2015
DOI: 10.1002/2015gl066465
|View full text |Cite
|
Sign up to set email alerts
|

Influences of source conditions on mountain wave penetration into the stratosphere and mesosphere

Abstract: We present atmospheric gravity wave (GW) measurements obtained by a Rayleigh/Raman lidar at Lauder, New Zealand, (45°S, 170°E) during and after the Deep Propagating Gravity Wave Experiment campaign. GW activity and characteristics are derived from 557 h of high‐resolution lidar data recorded between June and November 2014 in an altitude range between 28 and 76 km. In this period, strong GW activity occurred in sporadic intervals lasting a few days. Enhanced stratospheric GW potential energy density is detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 29 publications
9
75
2
Order By: Relevance
“…Orographic gravity wave variances are also strongly correlated with the zonal background wind at 40 km altitude (with ρ s varying between 0.6 and 0.8), which we attributed to the AIRS observational filter. However, in a recent study of gravity wave measurements by a Raleigh/Raman lidar at Lauder, New Zealand, Kaifler et al (2015) also found enhanced correlation of the observed stratospheric gravity wave activity with the stratospheric winds. Weaker correlations are found with respect to low-level winds at 2 km altitude (with ρ s varying between 0.2 and 0.4), but this may be mostly due to the fact that the low-level winds at the hotspots were rarely below the threshold required for launching waves.…”
Section: Discussionmentioning
confidence: 99%
“…Orographic gravity wave variances are also strongly correlated with the zonal background wind at 40 km altitude (with ρ s varying between 0.6 and 0.8), which we attributed to the AIRS observational filter. However, in a recent study of gravity wave measurements by a Raleigh/Raman lidar at Lauder, New Zealand, Kaifler et al (2015) also found enhanced correlation of the observed stratospheric gravity wave activity with the stratospheric winds. Weaker correlations are found with respect to low-level winds at 2 km altitude (with ρ s varying between 0.2 and 0.4), but this may be mostly due to the fact that the low-level winds at the hotspots were rarely below the threshold required for launching waves.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical time series for the hydrostatic "nonrotating" regime are shown directly above the top of the mountain (Figure 10d). Due to the smaller vertical group velocity c gz ≈ α U = 1 m·s −1 using Equation (22), the waves need about 11 h to propagate to an altitude of 40 km and to achieve a stationary state characterized by horizontal phase lines; see Figure 10d.…”
Section: Resultsmentioning
confidence: 99%
“…As α is very small, the ground-based horizontal group velocity is close to U. According to Equation (22), the wave energy is propagated upward and gains an increasing downwind component with decreasing α. The phase angle varies between 0 • for k −1 = U/ f and 90 • for k → ∞.…”
Section: Archetypal Regimes Of Vertically-propagating Internal Gravitmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest value zero means that the wave packet in question was detected in the selected interval only. Recently, this technique was developed and applied successfully to time series of ground-based Rayleigh lidar profiles and is described and discussed in detail by Kaifler et al (2015Kaifler et al ( , 2017.…”
Section: Two-dimensional Wavelet Analysismentioning
confidence: 99%